Analysis Of Plantation Company Performance Post-Covid-19 - AMBARITA, HOLPU RONAL; Manik, Rianta Chen Yohana; Hamdani, Fauzan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Oil palm is one of the leading plantation commodities in the Republic of Indonesia. The tropical climate facilitates the growth of oil palms domestically. In 2019, the Coronavirus Disease (COVID-19) pandemic spread throughout the world, including Indonesia. This event directly affected the country's environmental, social, political, and economic conditions. Oil palm plantation companies were also impacted by these conditions. The phenomena that occurred during the COVID-19 period and the post-pandemic recovery period motivated the researcher to determine the performance of oil palm plantation companies in Indonesia. The research method used is a descriptive analytical tool, which provides a true picture of the research object based on the data and facts presented. The data are then collected, processed, and analyzed to draw conclusions. The object of this research is a list of plantation companies that publish financial reports on the Indonesia Stock Exchange (IDX). The financial performance of five oil palm plantation companies following the Covid-19 pandemic shows positive developments, or improvements, as evidenced by increasing trends in net sales, cost of goods sold, gross profit, cost of goods sold activities, profit and loss elements, other transaction activities, and asset value.